Efek Ekstrak Daun Kersen (Muntingia calabura L.) terhadap Kadar TNF-α pada Tikus Wistar Model Gout Artritis Akut - Parisa, Nita; Tantoro, Valyn T; Adenina, Masayu S; Prananjaya, Bintang A; Saleh, Masagus I; Theodorus (Universitas Kristen Maranatha, 2025)
The inflammatory condition, marked by pain, swelling, and elevated TNF-α levels, prompted the exploration of cherry leaves' flavonoids, known for their anti-inflammatory properties. An in vivo experimental study with a pre-and post-test control group design was conducted to compare the efficacy of cherry leaf extract (Muntingia calabura L.) in the Wistar rat model of acute gout arthritis. Five treatment groups (negative control (Na-CMC 0,5%), positive control (Colchicine), cherry leaf extract dose 200mg/kgBW, cherry leaf extract dose 400mg/kgBW, and cherry leaf extract dose 800mg/kgBW) were administered to Wistar rats to compare their ability in reducing TNF-α levels. Results revealed the extract's significant efficacy in reducing TNF-α levels at all doses compared to negative control. There is no significant difference among the three different doses compared to colchicine as a positive control. In conclusion, cherry leaf extract demonstrated significant efficacy as an anti-inflammatory agent by reducing TNF-α levels in acute gout arthritis rat models with the most efficient dose of 200mg/kg BW.